Framing Undergraduate Public Health Education as Liberal Education: Who Are We Training Our Students To Be and How Do We Do That? - Kiviniemi, Marc T.; Mackenzie, Sara L. C. (Frontiers in Public Health, 2017)
The rapid development of the undergraduate major in public health over the past 15 years has led to a debate about the most appropriate framing for the degree. Should it be viewed as a liberal education degree (akin to academic disciplines like psychology and political science) or as a professional training degree (akin to disciplines like nursing and management)? This paper presents an overview of both the liberal education and the professional training degree approaches to the undergraduate public health degree. The reality of public health work in a modern era and the constraints on undergraduate-level training lead to our conclusion that the liberal education framing is a more optimal way to design the degree program. Such a framework optimizes career opportunities, especially long term opportunities, for graduates, acknowledges the reality of the complex and diverse career paths that one can take under the general umbrella of public health, and accounts for the important role of critical thinking skills in undergraduate education. Ultimately, the distinction between liberal education and professional training may be fuzzier than the debate often highlights — an intentional, well-designed and thoughtfully implemented undergraduate public health curriculum can address the range of student needs underlying both the liberal education and professional training approaches to the degree, thus optimizing both learning goals and career outcomes for undergraduate public health students.